Arctic origin and domestic development of Chinook Jargon - Samarin, William J. (De Gruyter, 1996)
It is entirely appropriate that Chinook Jargon was included in a conference on Arctic pidgins even though its linguistic form has little to do with the Arctic. Furthermore, the Chinook were not themselves Arctic people but lived at the end of the eighteenth century (and into the nineteenth century, of course) at the mouth of the Columbia River in what is today the state of Washington.